1997
DOI: 10.1101/gad.11.22.3096
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activity of Pannier is regulated negatively by heterodimerization of the GATA DNA-binding domain with a cofactor encoded by the u-shaped gene of Drosophila

Abstract: The genes pannier (pnr) and u-shaped (ush) are required for the regulation of achaete-scute during establishment of the bristle pattern in Drosophila. pnr encodes a protein belonging to the GATA family of transcription factors, whereas ush encodes a novel zinc finger protein. Genetic interactions between dominant pnr mutants bearing lesions situated in the amino-terminal zinc finger of the GATA domain and ush mutants have been described. We show here that both wild-type Pannier and the dominant mutant form act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
163
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(178 citation statements)
references
References 54 publications
5
163
0
4
Order By: Relevance
“…In addition, recent studies have suggested that FOG-1 can interact with either GATA-1 or GATA-2 to promote megakaryopoiesis, arguing against the previous notion that FOG-1 functions independently in this process (5). Furthermore, in Drosophila, Ush repression of heart and sensory bristle development apparently requires the GATA binding partner Pannier (6,37). Unequivocal examples of FOG-independent functions have not been found.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, recent studies have suggested that FOG-1 can interact with either GATA-1 or GATA-2 to promote megakaryopoiesis, arguing against the previous notion that FOG-1 functions independently in this process (5). Furthermore, in Drosophila, Ush repression of heart and sensory bristle development apparently requires the GATA binding partner Pannier (6,37). Unequivocal examples of FOG-independent functions have not been found.…”
Section: Discussionmentioning
confidence: 71%
“…In general, FOG proteins bind the N-terminal zinc-finger of their respective GATA partners. This interaction modifies GATAregulated transcription in a variety of tissues and in taxa ranging from flies to humans (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Hematopoietic coregulators of GATA factors may include members of the Runx family.…”
mentioning
confidence: 99%
“…We therefore sought to estimate the affinity of the 15 N-labeled USH-F9⅐Pnr-NF interaction by analyzing our 1 H, 15 N HSQC titration data. Several USH-F9 resonances (Cys-14, Val-21, and Tyr-31) were in fast exchange, and independent fitting of their chemical shift changes using a simple heterodimerization model (Equation 5 and Fig. 3A) gave an average K a of (1.3 Ϯ 0.6) ϫ 10 4 M Ϫ1 .…”
Section: Resultsmentioning
confidence: 99%
“…The peak position for a resonance in intermediate exchange does not accurately reflect the weighted average between the free and bound states of the protein and can no longer be determined by a simple expression such as Equation 5. However, the amplitude of a signal from USH-F9 as a function of frequency for a particular Pnr-NF concentration can be determined from the imaginary component of the complex quantity G() (34), which is given by…”
Section: Methodsmentioning
confidence: 99%
“…, an amorph allele of emc (Brown et al 1995); Bar 1 (B 1 )/FM7, a dominant gain-offunction mutation generated by duplication of the 16A region containing BarH1 and BarH2 genes, referred to as Bar (B); Df(1)Bar , a deficiency in which both B genes are deleted (Higashijima et al 1992); sgg 1 /FM7a Dp(1;2;4) w 1 , a lethal recessive X-ray allele of sgg (Bourouis et al 1990); Df (2L) BSC7/CyO, UAS-pnr D4 (Haenlin et al 1997); y w; FRT82, pnr vx6 / TM6B (Heitzler et al 1996); UAS-pnr ENR , a dominant-negative form of pnr, which contains the repressor domain from Engrailed (amino acids 2-298) (Klinedinst and Bodmer 2003); UAS-ush (Fossett et al 2001); Df (3L) Iro-C DFM3 FRT80/TM6B, a deficiency for ara, caup, and promoter for mirr, UAS-ara (Gomez-Skarmeta et al 1996); UAS-mirr (McNeill et al 1997); y w ey-FLP (Newsome et al 2000); and pnr-GAL4 . All stocks are described in FlyBase (http:/ /flybase.bio.indiana.edu).…”
mentioning
confidence: 99%